The standard of care in traditional medicine and modern medicine - Boukerroucha, Halima; Asmaa , Ibrahim Atiyah (Asian & African Research Centre, 2016)
This study aims to present the standard of care used in both traditional and modern medicine with attempts to compare and contrast between each of them. The issue of concern is whether practitioners in both medicine are required to adhere and follow the same standard of care or each one has its own standard differ from other. This should follow by necessity to define these standard in either field to the general public, patients, and practitioners in order to protect them. Such standard is considered as the cornerstone in the field of medicine; its practitioner is, thus, required to be committed in acting in accordance to the given standard and failure to do so could result to certain legal implications and actions. Therefore, practitioners in the field of medicine are held liable if found to be negligent in any of the given standard of care. So, to examine this issue, this study explains the definition of the standards of care in traditional and modern medicine firstly. Following by stating the limitations of the given standards of care in each field of medicine secondly. At the latest, it will mention the critical view of standard of care in both medicine. Overall, the main outcome of this study is that the given standard of care whether in the field of traditional or modern medicine is different in either field. This professional differences lead absolutely to vary their legal principles and rules in malpractice cases. Because of a very unique philosophy, set of principles, definitions, and standard for traditional medicine in contrast to modern medicine.